Manajemen Kelas yang Efektif: Strategi Pengelolaan dan Perbedaan Pendekatan Instruksional serta Transaksional dalam Pembelajaran - Wiranda, Wiranda; Jilham, Muhammad Aqsal; Saksitha, Deassy Arestya (Indonesian Journal of Islamic Educational Management, 2024)
Manajemen Kelas yang Efektif: Strategi Pengelolaan dan Perbedaan Pendekatan Instruksional serta Transaksional dalam PembelajaranTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//